Hidrociclonagem aplicada ao processamento físico de concentrado fosfático contendo minérios de terras raras - Silva, Jéssica Terra Teodoro da (2019)
Rare earth elements (REEs) have high market value, great applicability and, on the other hand, have low recycling rates and are difficult to replace in their applications. They are produced by a small number of countries and their supply becomes subject to oscillations based on political or strategic issues. In 2017, Brazil was the world's second largest reserve of rare earth elements, losing only to China, which has an estimated reserve of 44 million tons and was responsible for the production of 80.76% of the RREs consumed worldwide. Most Brazilian reserves of rare earth oxides are associated with phosphates, one of the raw materials in the fertilizer industry. Currently, apatite, fluorides, silica, limestone, titanium and gypsum are plowed from such reserves and the minerals containing rare earth oxides (REOs) are lost in the tailings or applied to the soil with fertilizers, because of the difficulty of separating such ores and economic viability. Thus, the granulochemical characterization of the phosphate concentrate from a fertilizer-producing company, whose ore was drained in Catalão (GO), was initially performed. Subsequently the physical concentration was achieved by means of modular mini-hydrocyclones with a characteristic diameter of 30 mm. It was studied how the geometric and operational parameters of the equipment influence the separation of the fraction smaller than 25 μm by overflow. Empirical correlations for capacity, liquid ratio and efficiency in function of cone angle, length of cylindrical region, underflow diameter, pressure and volumetric feed concentration were obtained. It could be observed that the efficiencies oscillated around the separation limit of the equipment, of approximately 96%, including operating with the solids concentration equal to 5% by volume. A significant drop in efficiency occurred at concentrations close to 9%, when the hydrocyclone started to operate in dense regime. In relation to the concentration of REOs in the overflow it was observed that the influence of the density and shape of the existing minerals in the sample, the collection of fractions larger than 25 μm and the existence of circulatory flows, was observed. However, a concentration of REOs, at least 79 % higher than that of feed, was obtained.